Restorasi mahkota pasak pada gigi dengan jarak serviko-oklusal pendek Dowel crown restoration on tooth with short cervico-occlusal distance - Setyawan Bonifacius; Sri Wahyuningsih Rais (Journal of Dentomaxillofacial Science, 2012)
Dowel crown restoration is a restoration which is often performed by dentists in daily practice. Dental crowns requirethe dowel crown restoration due to several factors including the crown damage cause has been very severe. Dowelcrown restoration usually consists of two parts, namely dowel with core and crown restoration on it. The core must behigh enough in cervico-occlusal direction to obtain sufficient retention for the attachment of the crown. In some casesthis condition cannot be fulfilled because the cervico-occlusal distances are too short resulting from extrusion of thetooth. This paper is reporting a case of management tooth maxillary second premolar with limited cervico-occlusaldimension with dowel crown restoration in one unit. The technique was a combination of direct and indirect method.The result was an accurate and retentive dowel crown, and has a good aesthetic.